2015
DOI: 10.1590/1679-78251919
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical investigation of lattice-walled cylindrical shell under low axial impact velocities

Abstract: This research was an experimental and numerical investigation of the cylindrical expanded Sheets under impact loading. Two types of absorbers with different cell angles were examined (i.e.  =0 and  =90). The experiments were performed using the drop hammer setup, and the numerical simulations were conducted by ABAQUS. In this study, the type of collapse, force-displacement diagrams, the crushing length, and the absorbed energy were investigated. The experimental and numerical results were compared, and it wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 16 publications
(17 reference statements)
0
5
0
Order By: Relevance
“…3,5 Metal meshes, due to their durability and metallic properties, are another promising collecting medium that have gained great interest. The applications of metallic structures (woven, 11,12 knitted, 5,13 or expanded [14][15][16] ) are not only limited to fog collectors but also in energy absorption applications. [17][18][19] In fog collection applications, the efficiency of the collectors is influenced by the fog liquid water content, the fog droplet size distribution, the wind speed and the collector characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…3,5 Metal meshes, due to their durability and metallic properties, are another promising collecting medium that have gained great interest. The applications of metallic structures (woven, 11,12 knitted, 5,13 or expanded [14][15][16] ) are not only limited to fog collectors but also in energy absorption applications. [17][18][19] In fog collection applications, the efficiency of the collectors is influenced by the fog liquid water content, the fog droplet size distribution, the wind speed and the collector characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…The use of a static loading is not sufficient to predict the behaviors of cement and concrete composites against impact loading. Moreover, perforated steel sheets have high energy absorption capacity [30][31][32][33]. The combination of perforated steel sheets and self-compacting fiber concrete composites can be studied as a combined system.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the tubes with zero degree angle cells had a symmetric collapse mechanism and increase in the size of the cells decreased the peak crushing force and E a capacity. Hatami and Damghani Nouri [16] presented experimental and numerical investigation of a lattice-walled cylindrical shell. In their study, the type of collapse, force–displacement diagrams, crushing length, and absorbed energy were investigated.…”
Section: Introductionmentioning
confidence: 99%